Bioestimulante como atenuador de estresse salino na cultura da abobrinha italiana (cucurbita pepo l.) - Souza, Maria Williane de Lima (2018)
The objective of this work was to assess the effect of seeds treatment with biostimulant Stimulate® on the culture of zucchini, cv. Italian Caserta, under saline stress. The research was accomplished in three stages, in which we assessed the use of biostimulant in pre-treatment of seeds, in the seedlings production, in the growth and production of zucchini. The first experiment was accomplished in laboratory, assessing the performance of seeds treted with bioestimulant, through soaking curve and germination test, using completely randomized design, in factorial scheme 3x5, with three times of seeds‟ soaking (6, 8 and 10 hours) and five concentrations of biostimulant (0; 5; 10; 15 and 20 mL L-1), with four repetitions. The second experiment was accomplished in greenhouse, assessing the use of biostimulant and saline stress in the production of zucchini seedlings, being analyzed the growth, dry mass accumulation and chlorophyll level. The experiment was accomplished in completely randomized design, in factorial scheme 2x6, with two levels of salinity in water used for irrigation (0,5 and 5,0 dS m-1) and six ways to administer the biostimulating (B1- absence, B2- seed, B3- Seed + foliar 5 mL L-1, B4- Seed + foliar 10 mL L-1, B5- Foliar with 5 mL L-1 and B6- Foliar with 10 mL L-1), with four repetitions. The third experiment was accomplished in experimental area, in order to assess the growthing, production and quality of fruits of zucchini cv. Italian Caserta according to saline stress and use of biostimulant. The treatments used were the same used in the later experiment, differing only with respect to the ways of administering: B3, B4, B5 e B6: application by seed + foliar (10 mL L-1 during flowering), seed + foliar (10 mL L-1 at 20 and 30 days after sowing), foliar (10 mL L-1 during flowering) and foliar (10 mL L-1 at 20 and 30 DAS), respectively. During this stage, plants were assessed with respect to growthing, dry mass accumulation, production and physic-chemical properties of fruits. In the three experiments, data obtained were submitted to variance analysis and we accomplished the deployment of factors for the variables presenting significant answer to the interaction among factors. Statistical analysis of data showed that the use of biostimulant was not efficient to inhibit the deleterious effect of salinity over most variables analyzed. However, the use of biostimulant is efficient to enhance the production of zucchini fruit, regardless of quality of water used in irrigation